Numerical Analysis of Dead Load Shear Force Distribution in Webs of Multicell Inclined Web Box-Girder Bridge - Xingwei Xue; Meizhong Wu; Zhengwei Li; Peng Zhou (Advances in Civil Engineering)
Moment and shear load distribution are important in bridge design. Most existing studies have focused on the distribution of girders under vehicle loading, neglecting the dead load distribution between the webs of multicell box-girders. Through the “Sum of Local Internal Forces” function, the shear force of each web in the multicell box-girder 3D finite element model was extracted and analysed using the dead load shear force distribution factor. The research parameters include the slope of the web, support condition, and cell number with respect to the dead load shear force distribution factor. The results indicate that the dead load shear distribution in the webs of multicell box-girders is uneven. The outermost inclined web bears a shear force greater than the average shear force, which must be considered in bridge design.